2015
DOI: 10.1053/j.ackd.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Relationship Between CKD and Ambulatory Blood Pressure Patterns

Abstract: Hypertension and chronic kidney disease (CKD) frequently coexist, and both are risk factors for cardiovascular events and mortality. Among people with hypertension, the loss of the normal fall in nighttime BP, called nondipping, can only be diagnosed by ambulatory BP monitoring (ABPM), and is a risk factor for cardiovascular events. The pathophysiology of nondipping is complex, and CKD is an independent risk factor for non-dipping. In fact, non-dipping can be seen in as many as 80% of people with CKD. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 72 publications
0
25
2
2
Order By: Relevance
“…Non-/reverse-dipping was also shown to be a risk factor for cardiovascular events and correlated with markers for cardiovascular events in CKD patients (101415162829). Multiple factors cause suppressed nighttime BP decrease, such as older age, race, autonomic dysfunction, abnormal sleep-wake cycle, and sodium sensitivity (30). In addition, Feldstein et al (31) reported that non-dippers were associated with elevated serum Ca in elderly essential hypertensive patients with mild-to-moderate CKD, and Kanbay et al (32) reported that the non-dipper clinical profile is related to serum Ca, P, and PTH in hypertensive patients with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Non-/reverse-dipping was also shown to be a risk factor for cardiovascular events and correlated with markers for cardiovascular events in CKD patients (101415162829). Multiple factors cause suppressed nighttime BP decrease, such as older age, race, autonomic dysfunction, abnormal sleep-wake cycle, and sodium sensitivity (30). In addition, Feldstein et al (31) reported that non-dippers were associated with elevated serum Ca in elderly essential hypertensive patients with mild-to-moderate CKD, and Kanbay et al (32) reported that the non-dipper clinical profile is related to serum Ca, P, and PTH in hypertensive patients with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure values obtained by ABPM, better than casual measurements, correlate with organ damage of hypertension [11][12][13]. With www.ah.viamedica.pl the twenty-four hour blood pressure monitoring it has become possible to analyse the circadian blood pressure profile.…”
Section: Discussionmentioning
confidence: 99%
“…Data from recent years show that patients with hypertension characterized as "non-dippers" are burdened with a higher risk of cardiovascular events [13]. Evaluation of circadian blood pressure profile may identify CKD patients at high risk of complications of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Kod zdravih osoba, KP pokazuje noćni pad od približno 10-20%, koji je regulisan delovanjem nekoliko faktora uključujući diurnalne varijacije u autonomnoj funkciji nervnog sistema, ekskreciju soli i RAAS. Poremećena regulacija ovih sistema u HBB vodi "non-dipping-u" ili čak porastu KP u toku noći, koji je udružen sa povećanim KV morbiditetom i mortalitetom i rizikom progresije HBB [55]. Adekvatno sniženje KP redukuje proteinuriju čime usporava opadanje JGF i smanjuje rizik KV događaja.…”
Section: Farmakološke Intervencije Antihipertenzivna Terapijaunclassified